Study of Depression and Its Associated Factors among Women Living with HIV/AIDS in Coastal South India. (21st June 2012) - Unnikrishnan, B.; Jagannath, Vinita; Ramapuram, John T.; Achappa, B.; Madi, D.
Abstract : Background . Depression is one of the most prevalent psychiatric diagnoses seen in HIV-positive individuals. Women with HIV are about four times more likely to be depressed than those who are not infected. Aims . To assess the sociodemographic and clinical correlates of depression among women living with HIV/AIDS. Setting and Design . One public and one private hospital in Mangalore, Coastal South India, and cross-sectional design. Methods and Materials . Study constituted of 137 HIV-positive women, depression was assessed using BDI (Beck Depression Inventory), and social support was assessed using Lubben Social Network Scale. Statistical Analysis . All analysis was conducted using SPSS version 11.5. Chi-square test withP value less than 0.05 was taken as statistically significant. Results . Among 137 HIV-positive women, 51.1% were depressed. Around 16% were having moderate to high risk for isolation. Depression was statistically significant in rural women, widowed women, and lower socioeconomic class women. Conclusion . Depression is highly prevalent among women living with HIV which is still underdiagnosed and undertreated, and there is a need to incorporate mental health services as an integral component of HIV care.